2022
DOI: 10.1039/d2fo02034c
|View full text |Cite
|
Sign up to set email alerts
|

Two novel lactic acid bacteria,Limosilactobacillus fermentumMN-LF23 andLactobacillus gasseriMN-LG80, inhibitedHelicobacter pyloriinfection in C57BL/6 mice

Abstract: Helicobacter pylori (H. pylori) is one of the most prevalent pathogens globally, and long-term infection causes various gastrointestinal diseases such as gastritis and even cancer. In the present study, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…and Lactobacillus spp. have been found to significantly decrease the abundance of Helicobacter, one of the most common pathogens globally associated with gastritis and cancer, by 90% and 83%, respectively, in an infected mouse model (Zhao et al, 2022a). Moreover, Limosilactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…and Lactobacillus spp. have been found to significantly decrease the abundance of Helicobacter, one of the most common pathogens globally associated with gastritis and cancer, by 90% and 83%, respectively, in an infected mouse model (Zhao et al, 2022a). Moreover, Limosilactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…60 Furthermore, persistent infection with H. pylori can induce the production of ROS and pro-inflammatory cytokines, including IL-1β, IL-6, IL-8, and TNF-α, which are involved in the augmented mucosal damage and development of mucosa-associated lymphoid tissue (MALT) lymphoma and gastric adenocarcinoma. 62 Substantial evidence has reported that LAB can impair the pathogenic virulence of invading pathogens, decreasing inflammatory cytokine production as well as alleviating mucosal damage 20,21,87,88 Napoli et al reported that EFV12 derived from Lactobacillus gasseri SF1109 could interfere with mitogen-activated protein kinase signaling pathways by binding lipopolysaccharides and preventing lipopolysaccharide (LPS) attachment with Toll-like receptor 4. 89 Furthermore, supplementation with various concentrations of PLA in basal diet enhanced the level of IgY (immunoglobulin Y) in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus and Bifidobacterium are the two most common species found in probiotic products such as yogurt ( Xiong, 2018 ; Ye et al, 2020 ). In the past, the positive effects of dairy products such as yogurt on digestion were proven ( Whiteside et al, 2021 ; Zhao et al, 2022 ). Other species accessible on the market include Bacillus spp., Enterococci , E. coli , Weissella spp., and Saccharomyces .…”
Section: Alternative Therapiesmentioning
confidence: 99%